Frauen-Migrationen und sozialer Wandel in Afrika. Das Beispiel Kenya - Vorlaufer, Karl (ERDKUNDE, 1985)
An extremely high sex-ratio (males per100 females) had been the outstanding characteristic feature of colonial urban development in Kenya. It was mainly young men who participated in a migration from rural areas to urban centres in order to take part in the urban migrant labour market for a limited period of time, then returning to the rural settlement. In this way a pattern of circular migration developed between town and countryside and vice versa. The living costs of migrant labour had to be covered from time to time by the traditional subsistence economy in the migrants’ home areas - e.g. during childhood or periods of sickness, after retirement or where the migrant’s family remained in the home areas. Traditionally only very few women migrated to urban centres. Not only were they needed to work on the fields at home, but the low wages in town, a severe shortage of housing and a very limited number of openings in the modern sector employment on offer to female migrants contributed to holding back females on their husbands’ shambas. In addition to this, the bridewealth system strengthened the ties of women to rural areas where they could play an active role working on the shamba and by being mothers of as great a number of children as possible. It can not be observed that in recent times an ever-increasing number of females is also attracted by chances of improving their economic well-being by moving to urban centres. Reasons for this additional migration-wave are to be found in a general weakening of traditional values and authorities, the increasing land shortage and the resulting population pressure in he rural areas, which are factors that do in fact force women to migrate to towns. When compared to the number of men migrating to towns, the number of migrating women, though fairly large, is still lower. On the other hand, women, once in town, will more often tend to stay in town and will not participate in the circular migration mentioned above. Recent statistics indicate that female net out-migration from many rural districts exceeds that of men. In this way, rapid urban growth can be said to be mainly the result of women migrating to towns and subsequently staying in them. The patterns of migration vary between districts and ethnic groups in accordance with spatially different social distances between rural and urban ways of life. The sizeable female migration movement should not be seen as an indication of female emancipation, i.e. women taking a more active part in an effort to shape their own lives. It is in fact mainly women who have to carry the burden of social change. The decreasing importance of traditional authorities and values will also result in less effective systems of social security for women in tribal areas. It can therefore be stated that the influx of women into Kenya’s urban centres is to a great extent the result of an ever growing reduction to poverty of a substantial part of Kenya’s female population.